Farmers' Adaptation Strategies, Coping Behaviour and Barriers to Effective Adaptation to Current Climatic Risks: A Study on Sundarban Region - Shantanu Rakshit , R. N. Padaria and S. Bandyopadhyay, (Indian Journal of Extension Education, 2016)
The Sundarban region is one of the worst climate change hotspots that influences the lives and livelihoods of millionsof people. This study was designed to examine the farmers' coping behaviour, adaptation strategies, and barriers toeffective adaptation to current climatic risks. The study was conducted in the Sundarban Region of West Bengal state. Twovillages from Kultoli block of South 24 Parganas district were selected. With 40 respondents from each village, total 80respondents were selected randomly. The main reported adaptation strategies were crop diversification, change incropping sequence, increase of bund height, diversification of income and livelihood. Farmers have shifted from fieldcrops and fruit orchards to vegetable cultivation. Income from agriculture, fishing and livestock rearing have decreasedand people forced to rely more on daily labour.Mainly reported coping strategies were migration, reduction of daily mealin amount and frequency, work as a daily labourand alternate income generating activity. The main barriers for effectiveadaptation to current climatic risks were lack of resource, lack of knowledge, lack of institutional support, poor extensionsystem and lack of infrastructure.